Determination of Gestational Age by Fetal Kidney Length Measurement After the 20th Week in Healthy Women With Uncomplicated Pregnancy in Tertiary Care Centre - Joshi, Birendra Raj; Chaurasia, Akash Kumar; Khanal, Umesh Prasad (Journal of Nepal Paediatric Society, 2021)
Introduction: Various organs are measured to estimate the gestational age of fetus. Sonographically derived parameters used to date pregnancy include crown rump length, biparietal diameter, head circumference, femoral length and abdominal circumference. Fetal kidney length, transcerebellar diameter and placental thickness are emerging as new parameters and are claiming to be more accurate in certain situations. In Nepalese context fetal kidney length has not been studied yet so this study was done to fill this need. Methods: Obstetric sonography was performed in 108 pregnant women with uncomplicated pregnancy to evaluate the efficacy of FKL as a measure to calculate the predicted gestational age. Gestational age ranged from 20 weeks to term. Only patient with known LMP and previous history of normal menstrual cycle were included in the study. Results: The study showed mean fetal kidney length at 20 - 24, 25 - 29, 30 - 34 and 35 - 37 weeks gestation as 22.5 ± 0.5, 26.9 ± 0.7, 32.32 ± 0.7 and 36.3 ± 0.6 respectively. Overall in combined second and third trimester, fetal kidney length showed strong linear correlation with gestation age with highest significant Pearson correlation coefficient of 0.989 as compared to other parameters (BPD = 0.986, HC = 0.976, AC = 0.971, FL = 0.984). Conclusions: Fetal kidney showed strongest linear correlation with clinical gestational age and it also demonstrated positive correlation with biparietal diameter, head circumference, abdominal circumference and femur length. Therefore fetal kidney length can be used as a reliable parameter for determination of gestational age.